OLDER SUBJECTS WOULD MORE LIKELY USE SMARTPHONE APPLICATIONS FOR HYPERTENSION THAN MIDDLE-AGED PATIENTS. DATA FROM THE 2017 WORLD HYPERTENSION DAY IN CROATIA. (June 2018) - Dapic, K.; Domislovic, V.; Milicic, B.; Drenjacevic, I.; Gulin, M.; Grba, E.; Cavrak, V. Herceg; Jelakovic, A.; Josipovic, J.; Kralj, V.; Leko, N.; Lugovic, N.; et al.
Abstract : Objective: Smartphone-based applications have been considered as a great opportunity to increase adherence and improve control of hypertension. However, several important items should be elucidated before applying this armature in real life. One of first tasks is to identify target population which would most likely use these applications. This was the aim of our study which was conducted in a group of individuals (aged 18 years or older) participating in the 2017 World Hypertension Day in Croatia. Design and method: This study was organized by the Croatian Society of Hypertension on 2017 World Hypertension day at 26 sites in 5 cities in Croatia (hospital open points, central squares and pharmacies). Along with BP measurement, a short questionnaire on hypertension awareness/salt intake/smartphone use was completed at the time of the interview by the physicians, trained nurses, pharmacist and medical students. Results: A total of 2175 subjects, 873 (40.1%) men, 1211 (59.9%) women were examined. Smartphones were used by 36.4% examined subjects (no gender difference), average age was 53.9 (15.6), and in the group of subjects who are using smartphone men were older (56.8(15.2) vs. 52.0(15.6); p < 0.001). We analyzed utilization of smartphone in several age categories and significant difference was found among age groups: under 35 years, 35–55 years, 55–70 years and above 70 years (87.5%, 70.4%, 33.6% and 13.3%, respectively). In the whole group 32.1% of individuals answered positive on the question of whether they would use mobile application for blood pressure control (no gender difference). Average age of those who answered positive was 55.7 (15.2) years (m vs. 58.1(15.2) vs. 54.2(15.1), p = 0.013). Significant difference in positive answer was obtained among age groups: under 35 years, 35–55 years, 55–75 years and above 70 years (58.7%, 57.7%, 32.4%, 13.3%, respectively, p < 0.001). Conclusions: In this large cohort we found that one-third of subjects having smartphone would use mobile applications for hypertension. Interestingly, all subjects older than 55 years and 58 % of subjects younger than 55 years who own a smartphone would like to use mobile applications for BP control.